Development and Application of an Aerosol Model Under a Severe Nuclear Accident - Yuan, Xianbao; Wei, Jingyu; Zhang, Binhang; Guo, Yuefeng; Shi, Qiang; Guo, Pan; Yang, Senquan; Tan, Chao (Frontiers in Energy Research, 2022)
Radioactive aerosol will transport in the containment and also will leak into the environment under a severe nuclear accident. Thus, it is of great significance for predicting the behavior of aerosol under a severe nuclear accident. In order to satisfy the analysis of aerosol behavior, an improved multi-component aerosol model is developed to analyze the radioactive aerosol behavior, which improved section numbers and update aerosol particle density at each time step. The model's dependability is confirmed to use benchmark and experiments values. An excellent agreement can be observed between simulation and benchmark. On this premise, the circumferential large-break water loss accident is chosen to explore the behavior of radioactive aerosol in the containment. The findings show that in the event of a large-break water loss accident, the aerosol is mostly deposited on the structure's surface due to gravity. According to a comparison of the influence of aerosol natural deposition mechanisms on the distribution of diameter particles, Brownian diffusion, thermophoresis, diffusiophoresis, and gravity all have an effect on aerosol in the range of 0.01μm-0.03μm particles and the deposition of 2μm-20μm particles are mainly due to gravity. After comparing and evaluating the influence of aerosol density in the containment, it can be inferred that changed aerosol particle density lead aerosol particles coagulate into larger particle.